YUSUF AFANDI AL-YAHSAWI: BIOGRAPHICAL INSIGHTS FROM THE KLYCHEV FAMILY MANUSCRIPT COLLECTION - Hanmurzaev, Ismail Ibragimovic; Osmanova, Milena Nurievna (History, Archeology and Ethnography of the Caucasus, 2025)
This article explores certain aspects of the life and work of Yusuf Afandi Klychev (al-Yahsawi), a distinguished Dagestan scholar, political figure, theologian and poet from the mid-nineteenth century. These details have come to light through the examination of his manuscripts, now preserved by his descendants in Khasavyurt, Republic of Dagestan. Famous as one of Imam Shamil’s ideological opponents, Yusuf Afandi al-Yahsawi held significant respect among Dagestani scholars. At the same time, he was also marked by his broad outlook, cultivated by his time in the Life Guards Caucasian-Mountain Half-Squadron and his contacts with religious leaders from the Volga region and the Middle East during his Hajj pilgrimages. By studying the marginalia of Yusuf Afandi’s copy of al-Hariri’s Maqāmāt – which he made while stationed in Tsarskoye Selo and brought home to his village of Aksay after returning – it has been possible to determine the exact dates of his service in the imperial convoy and other key events in his life. In addition, this work has greatly expanded what is known about Yusuf al-Yahsawi’s family: the precise number of Yusuf Afandi’s children, their full names, and birth dates have been identified, and a family tree for the well-known Klychev kin in Zasulak Kumykia has been created.